A note on units in F_q SL(2, Z_3) - Maheshwari , S.; Sharma , R. K. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 512.5 Let R be a ring, and SL(2,R) be the special linear group of 2×2 matrices with determinant 1 over R. We obtain the Wedderburn decomposition of F_q SL(2,Z_3)J(F_q SL(2,Z_3)) and show that 1+J(F_q SL(2,Z_3)) is a non-Abelian group, where F_q is a finite field with q = p^k elements of characteristic 2 and 3.